Undang-undang Hak Cipta Nomor 28 Tahun 2014 dalam Prespektif Ekonomi Hukum Ekonomi Islam - Tarmidzi (Jurnal Hukum Islam, 2017)
This present study aims to explain what intellectual property rights in the conception of sharia law (Islamic economics) are and how the Protection of Copyright under the Law Number 28 of 2014 is in the perspective of Islamic economic law. It was a qualitative study by conducting an explorative analytical doctrinal research method in relation to the legal facts regarding the norms contained in the Law Number 28 of 2014 on the Protection of Copyright (HAKI) in the perspective of Islamic economic law. The consensus (ijma’) of fiqh Muslim scholars (ulema) asserts that the right of ownership of mind and creation towards the result of thought and its creations is a material possession. This is based on the source of the law of maslahah mursalah (common benefit) and in accordance with maqashid al-sharia (objectives of Islamic law) because the right of thought and creations of the mind associated with the nature of property (al-mal) can be transacted and inherited if the owner dies, becomes a will if it meets all the requirements of property in Islamic law, and has the same position as other halal property. Therefore, a person’s copyright/creative rights should receive the same legal protection as other rights.